Efficient Production of the PET Radionuclide 133La for Theranostic Purposes in Targeted Alpha Therapy Using the 134Ba(p,2n)133La Reaction - Santiago Andrés Brühlmann; Martin Kreller; Hans-Jürgen Pietzsch; Klaus Kopka; Constantin Mamat; Martin Walther; Falco Reissig (MDPI AG, 2022)
Targeted Alpha Therapy is a research field of highest interest in specialized radionuclide therapy. Over the last decades, several alpha-emitting radionuclides have entered and left research topics towards their clinical translation. Especially, 225Ac provides all necessary physical and chemical properties for a successful clinical application, which has already been shown by [225Ac]Ac-PSMA-617. While PSMA-617 carries the DOTA moiety as the complexing agent, the chelator macropa as a macrocyclic alternative provides even more beneficial properties regarding labeling and complex stability in vivo. Lanthanum-133 is an excellent positron-emitting diagnostic lanthanide to radiolabel macropa-functionalized therapeutics since 133La forms a perfectly matched theranostic pair of radionuclides with the therapeutic radionuclide 225Ac, which itself can optimally be complexed by macropa as well. 133La was thus produced by cyclotron-based proton irradiation of an enriched 134Ba target. The target (30 mg of [134Ba]BaCO3) was irradiated for 60 min at 22 MeV and 10-15 µA beam current. Irradiation side products in the raw target solution were identified and quantified: 135La (0.4%), 135mBa (0.03%), 133mBa (0.01%), and 133Ba (0.0004%). The subsequent workup and anion-exchange-based product purification process took approx. 30 min and led to a total amount of (1.2-1.8) GBq (decay-corrected to end of bombardment) of 133La, formulated as [133La]LaCl3. After the complete decay of 133La, a remainder of ca. 4 kBq of long-lived 133Ba per 100 MBq of 133La was detected and rated as uncritical regarding personal dose and waste management. Subsequent radiolabeling was successfully performed with previously published macropa-derived PSMA inhibitors at a micromolar range (quantitative labeling at 1 µM) and evaluated by radio-TLC and radio-HPLC analyses. The scale-up to radioactivity amounts that are needed for clinical application purposes would be easy to achieve by increasing target mass, beam current, and irradiation time to produce 133La of high radionuclide purity (>99.5%) regarding labeling properties and side products.